Pointwise regularity for solutions of double obstacle problems on metric spaces - Farnana, Zohra (MATHEMATICA SCANDINAVICA, 2011)
We study continuity at a given point for solutions of double obstacle problems. We obtain pointwise continuity of the solutions for discontinuous obstacles. We also show Hölder continuity for solutions of the double obstacle problems if the obstacles are Hölder continuous.